Learning From the 1991 Law Exams Incident - Stewart, GT (Taylor & Francis, 2019)
This article revisits a moment in the recent history of education in Aotearoa New Zealand when te reo Māori as a language of the university came under intense scrutiny. The original incident took place in 1991 in Hamilton, Aotearoa New Zealand, when two students of Waikato Law School wrote answers in te reo Māori to an examination question relating to the Treaty of Waitangi. The students later laid a formal complaint about how their answers had been marked, which resulted in a report by the committee appointed to investigate. This useful report is part of a rich archive on this incident, and the Law School itself, in relation to the aspiration to provide a ‘bicultural’ legal education. This article revisits the 1991 exams incident through this textual corpus, focusing on discussions about te reo Māori as an academic language. The 1991 law exams incident is a useful example for illuminating wider questions relating to bicultural education in Aotearoa New Zealand.
Keywords: Biculturalism; Bilingualism; Indigenous legal education; Te reo Māori (the Māori language); Waikato Law School